THE EFFECTIVENESS OF USING RECIPROCAL TEACHING ON THE READING COMPREHENSION TO THE SECOND GRADERS OF MTsN - Defiana, Nita (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
Reciprocal Teaching technique is effective in teaching reading comprehension. In this research the result showed that the studentsâ Mean score in teaching reading without using Reciprocal Teaching technique is only 75.00.While the studentsâ mean score after they are taught using Reciprocal Teaching technique was 82.17. The result of signifcant level is 0,07%. By comparing signifcant level 0,07% and t table at 0.05 %. It is known that signifcant level is bigger than t table = 0,07% >0.05 %. Itâs means that Ha which states that there is signifcant effect of using Reciprocal Teaching as a technique of teaching reading narrative text toward studentsâ reading comprehension of the second Grade students of MTs N Pulosari is accepted. Whereas Ho which states that There is no signifcant effect of using Reciprocal Teaching as a technique of teaching reading narrative text toward studentsâ reading achievement of the second grade students of MTs N Pulosari is rejected. Based on the explanation above, Reciprocal Teaching technique surely showed the real effectiveness in teaching reading comprehension of the second graders of MTs N Pulosari.